2011
DOI: 10.1097/mpa.0b013e31821f2715
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Expressions of AP-2α Splice Variants in Pancreatic Cancer

Abstract: Objectives The present study was conducted to evaluate the expression and function of AP-2α isoforms in pancreatic ductal adenocarcinoma. Methods AP-2α expression was evaluated at RNA level by reverse transcription-polymerase chain reaction and at the protein level by western blotting and immunofluorescence. Its function as a transcription factor was evaluated in transient transfection experiments: DNA binding properties by electromobility shift assay and transactivation capabilities by Luciferase assay. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…48 TFAP2A upregulation is a feature of other tumour types, such as neuroblastoma, pancreatic cancer and acute myeloid leukaemia. 49,50,51 In our in vitro models, TFAP2A knockdown resulted in slower cell growth showing the relevance of this transcription factor to HNSCC proliferation in vitro. This finding together with the observation that cetuximab has a synergistic effect is evidence that TFAP2A downstream targets could be new therapeutic markers for combination approaches that will result in prolonged disease control.…”
Section: Discussionmentioning
confidence: 55%
“…48 TFAP2A upregulation is a feature of other tumour types, such as neuroblastoma, pancreatic cancer and acute myeloid leukaemia. 49,50,51 In our in vitro models, TFAP2A knockdown resulted in slower cell growth showing the relevance of this transcription factor to HNSCC proliferation in vitro. This finding together with the observation that cetuximab has a synergistic effect is evidence that TFAP2A downstream targets could be new therapeutic markers for combination approaches that will result in prolonged disease control.…”
Section: Discussionmentioning
confidence: 55%
“…In this study, Sancho et al (2015) also showed that over-expression of MYC diminished stem celllike properties of the tumor samples in comparison with their normal counterparts. A possible mechanism by which MYC is down-regulated may be by TFAP2A, which was found to negatively regulate MYC [Gaubatz et al, 1995;Carri ere et al, 2011], and also a protein for which our analysis revealed to be up-regulated in pancreatic tumor samples (Fig. This was due to the fact that MYC plays significant roles in the up-regulation of metabolic processes, and the down-regulation of MYC allowed cells to survive under conditions of limited energy sources.…”
Section: Discussionmentioning
confidence: 76%
“…The down-regulation of MYC in different independent studies and the emergence of reports about its function in pancreatic ductal adenocarcinoma show a paradoxically complex regulatory mechanism for MYC which needs to be further clarified. A possible mechanism by which MYC is down-regulated may be by TFAP2A, which was found to negatively regulate MYC [Gaubatz et al, 1995;Carri ere et al, 2011], and also a protein for which our analysis revealed to be up-regulated in pancreatic tumor samples ( Fig. 1b).…”
Section: Discussionmentioning
confidence: 86%
“…It is critical to determine the timing in treatment that reversible epigenetic alterations develop to allow alternative therapies to be effective. Short term exposure to targeted therapies can induce reversible chromatin changes that will lead to resistance, while chronic exposure induces DNA methylation changes that are more steady and observed in stable resistant states (34).…”
Section: Discussionmentioning
confidence: 99%
“…In nasopharyngeal carcinoma, TFAP2A silencing in vitro and in vivo results in slower cancer cell proliferation and that patients with high tumor levels of the gene present poorer survival compared to those with lower expression (36). TFAP2A up-regulation is a feature of other tumor types such as neuroblastoma, pancreatic cancer and acute myeloid leukemia [32][33][34] . In our in vitro models, TFAP2A knock-down resulted in slower cell growth showing the relevance of this transcription factor to HNSCC proliferation in vitro.…”
Section: Discussionmentioning
confidence: 99%